2017
DOI: 10.1016/j.jpsychires.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depression and anxiety disorders in indigenous people of the Americas: A systematic review and meta-analysis

Abstract: Indigenous populations are considered at higher risk of psychiatric disorder but many studies do not include direct comparisons with similar non-Indigenous controls. We undertook a meta-analysis of studies that compared the prevalence of depression and anxiety disorders in Indigenous populations in the Americas with those of non-Indigenous groups with similar socio-demographic features (Registration number: CRD42015025854). A systematic search of PubMed, Medline, PsycInfo, PsycArticles, ScienceDirect, EMBASE, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 38 publications
0
60
0
1
Order By: Relevance
“…Mainly based on clinical interviews, no differences in the 12-month prevalence rates of mental distress appeared. However, indigenous groups were at higher risk of PTSD [14]. Social origins of mental health problems in aboriginal peoples relate to cultural discontinuity and oppression [15].…”
Section: Introductionmentioning
confidence: 99%
“…Mainly based on clinical interviews, no differences in the 12-month prevalence rates of mental distress appeared. However, indigenous groups were at higher risk of PTSD [14]. Social origins of mental health problems in aboriginal peoples relate to cultural discontinuity and oppression [15].…”
Section: Introductionmentioning
confidence: 99%
“…According to the United Nations Permanent Forum on Indigenous Issues, there are 70 countries with approximately 300 million Indigenous people who live and retain distinct languages, culture, and beliefs (Hall & Patrinos, 2012). However, a recently published systematic review and meta-analysis (Kisely et al, 2017) found that the rates of depressive disorders were not higher among the Indigenous people of the Americas, compared to non-Indigenous groups. Existing studies rarely include Indigenous controls to allow prevalence comparisons.…”
Section: What This Topic Addsmentioning
confidence: 94%
“…Existing studies rarely include Indigenous controls to allow prevalence comparisons. However, a recently published systematic review and meta-analysis (Kisely et al, 2017) found that the rates of depressive disorders were not higher among the Indigenous people of the Americas, compared to non-Indigenous groups. The study's results have to be considered with caution due to limitations such as a possible lack of accuracy when measuring the symptoms of depression with diagnostic tools not validated for use in Indigenous populations.…”
Section: What This Topic Addsmentioning
confidence: 94%
“…A recent meta-analysis covered 19 studies conducted in the Americas, all but three of which came from North America. 4 Of these, ten studies were from the United States and six from Canada. For inclusion in the review, studies had to have data on similar controls.…”
Section: Indigenous Peoples Of North Americamentioning
confidence: 99%